Do Early Life and Contemporaneous Macro-conditions explain Health at Older Ages? - France Portrait; Rob Alessie; Dorly Deeg (Tinbergen Institute, 2008)
The paper presents an approach which thoroughly assesses the role of early life and contemporaneous macro-conditions in explaining health at older ages. In particular, we investigate the role of exposure to infectious diseases and economic conditions during infancy and childhood, as well as the effect of current health care facilities. Specific attention is paid to the impact of unobserved heterogeneity, selective attrition and omitted relevant macro-variables. We apply our approach to self-reports on functional limitations of Dutch older individuals. Our analysis is performed using data from the Longitudinal Aging Study Amsterdam. The prevalence of functional limitations is found to increase in the nineteen-nineties, in part due to restricted access to hospital care.
Keywords: I12; J11; J17; 330; early life macro-conditions; contemporaneous macro-conditions; functional limitations; aging; Gesundheit; Alte Menschen; Gesundheitsversorgung; Institutionelle Infrastruktur; Lebensverlauf; Niederlande